2015
DOI: 10.1186/s13054-015-1081-8
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein as a biomarker in severe traumatic brain injury patients: a prospective cohort study

Abstract: IntroductionGlial fibrillary acidic protein (GFAP) may serve as a serum marker of traumatic brain injury (TBI) that can be used to monitor biochemical changes in patients and gauge the response to treatment. However, the temporal profile of serum GFAP in the acute period of brain injury and the associated utility for outcome prediction has not been elucidated.MethodsWe conducted a prospective longitudinal cohort study of consecutive severe TBI patients in a local tertiary neurotrauma center in Shanghai, China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 47 publications
(43 reference statements)
5
106
0
3
Order By: Relevance
“…Various biomarkers can be detected in the CSF and serum depending on the blood brain barrier (BBB) integrity after TBI. The biomarkers for astroglial injury in the brain are S100B and GFAP [26]. These two markers are found to be elevated in the CSF and serum after TBI and have a good predictive power for prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Various biomarkers can be detected in the CSF and serum depending on the blood brain barrier (BBB) integrity after TBI. The biomarkers for astroglial injury in the brain are S100B and GFAP [26]. These two markers are found to be elevated in the CSF and serum after TBI and have a good predictive power for prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…* Significantly different from Saline-TBI [Color figure can be viewed at wileyonlinelibrary.com] identifying successful therapeutic approaches to reduce TBI secondary injury (Di Battista et al, 2015). GFAP is an intermediate filament protein specific for astrocytes, and increased GFAP immunoreactivity is a sensitive astrocyte injury biomarker (Cikriklar et al, 2016;Lei et al, 2015;Mondello et al, 2016). GFAP protein is rapidly released into biofluids following cortical injury (Foerch et al, 2012;Y.…”
Section: Discussionmentioning
confidence: 99%
“…In 24- and 48-h samples, GFAP was detectable in a smaller number of patients, and the levels were only slightly elevated. A more recent study (Lei et al, 2015), which followed the levels of GFAP for 0–5 days after the injury, reported that the peak was detected at admission (0.5–4 h). Žurek and Fedora (2012) monitored children that had TBI, and they also found the highest levels of GFAP in the admission samples drawn <12 h after injury.…”
Section: Biomarkersmentioning
confidence: 98%